REVIVAL OF MILLETS INTRODUCTION IN PUBLIC DISTRIBUTION SYSTEM- IMPROVING ACCESSIBILITY AND CONSUMPTION - N. SASIREKHA (The Journal of Research ANGRAU, 2025)
The study was conducted in 2023 to investigate the integration of millets into India’s Public Distribution System (PDS) and evaluate the feasibility and impact of incorporating millets into the PDS across South India, particularly in states like Telangana, Tamil Nadu, Karnataka, Kerala, and Andhra Pradesh. The distribution of millet grains under PDS has increased significantly in states having millet programs. The findings reveal that states implementing millet initiatives have witnessed a notable increase in consumption within the PDS framework. Karnataka emerged as a leader in millet distribution, with approximately 35% of total consumption, followed by Tamil Nadu (25%) and Andhra Pradesh (23%). Advancing millet cultivation and promoting nutrition education programs is vital to support millets acceptability and consumption to a greater population in the country. The successful implementation of millet inclusion in PDS could serve as a model for other nations aiming to address similar challenges in food security and nutrition.